Implementation of Color in the Interior Design of the Pharmacy Laboratory through a Total Ergonomics Approach provides Comfort and Increases Focus in Work - Ida Mulyati, Made; Anatolia, Levi (Syntax Corporation Indonesia, 2025)
Interior design is not only limited to arranging the room to make it look attractive. There are fundamental reasons why we need interior design, which must be able to create a room that is harmonious, aesthetic, meets the demands of its activities and the psychological demands of its community so that the room is functional. The furniture and equipment facilities of the pharmaceutical laboratory have been standardized. For color standardization does not yet exist, it is necessary to analyze the color in the interior design of the pharmaceutical laboratory through a total ergonomics approach to be able to provide comfort and focus for staff. The method used is descriptive analysis method. Color psychology is a theory of color studies related to human psychology. To balance the room, it must also be considered the appropriate color implemented in interior design to achieve balance and harmony in the room. Designing the interior of a pharmaceutical laboratory is not just about implementing the colors we like, but must have sufficient meaning so that it can have an impact on behavior, mood, cognition, focus, and general association. For this reason, it is considered important to study the total Ergonomics approach in order to get the optimal improvement solution. The results of the analysis obtained colors that are suitable to be applied to the interior of the pharmaceutical laboratory include neutral colors of white, light gray, and may slightly apply black as an accent. Besides there are several companion colors to be combined with neutral colors including white heron, crystalline, windmill wings, golden straw, thunder. By implementing these colors, it can provide comfort and focus for laboratory staff to improve performance and productivity.